2013
DOI: 10.1002/rra.2655
|View full text |Cite
|
Sign up to set email alerts
|

Water Temperature Patterns Below Large Groundwater Springs: Management Implications for Coho Salmon in the Shasta River, California

Abstract: Elevated stream temperature is a primary factor limiting the coho salmon (Oncorhynchus kisutch) population in California's Shasta River Basin. Understanding the mechanisms driving spatial and temporal trends in water temperature throughout the Shasta River is critical to prioritising river restoration efforts aimed at protecting this threatened species. During the summer, the majority of streamflow in the Shasta River comes from large-volume, cold-water springs at the head of the tributary Big Springs Creek. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…Groundwater may modulate temperatures; for example, warm groundwater inflows have been found to enhance the growth of postemergent Chinook salmon (Mejia et al, ). Near the southern extent of the range for salmon, cooler groundwater inflows may enhance habitat suitability (Madej et al, ; Nichols et al, ). Though our sites are geographically near this boundary, persistent cool temperatures (<16.3 °C) within the stream suggested that temperature was not likely a critical factor for salmonid persistence here (Woelfle‐Erskine et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater may modulate temperatures; for example, warm groundwater inflows have been found to enhance the growth of postemergent Chinook salmon (Mejia et al, ). Near the southern extent of the range for salmon, cooler groundwater inflows may enhance habitat suitability (Madej et al, ; Nichols et al, ). Though our sites are geographically near this boundary, persistent cool temperatures (<16.3 °C) within the stream suggested that temperature was not likely a critical factor for salmonid persistence here (Woelfle‐Erskine et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the primary antinode developed at the mouth of Big Springs Creek less than 6 hr of travel time downstream. The consistent geospatial location of this antinode can be attributed to an abrupt change in channel geometry from the wide and shallow Big Springs Creek to the narrower and deeper Shasta River (Nichols et al, ). Under the largely steady flow conditions in Big Springs Creek and the Shasta River, this abrupt increase in mean water depth effectively truncates the magnitude and range of observed downstream water temperatures.…”
Section: Discussionmentioning
confidence: 89%
“…Historically, surface runoff from direct precipitation and snowmelt in the Klamath Mountain's headwaters mixed with voluminous groundwater spring sources, creating a complex hydrologic regime characterized by stable baseflows augmented by seasonal runoff. However, due to upstream water storage and flow regulation (see Null, Deas, & Lund, for a description of surface water infrastructure in the Shasta River basin), streamflow in the Shasta River below Dwinnell Dam and Lake Shastina is derived predominantly from discrete springs discharging cool (11–13°C) and nutrient‐rich groundwater (Dahlgren et al, ; Lusardi et al, ; Nichols et al, ; NRC, ). The limited annual precipitation (24–46 cm year −1 ; NCRWQCB, ) in the Shasta River basin infiltrates Quaternary basalts and basaltic andesites of the High Cascades bounding the Shasta River to the north and east (Blodgett, Poeschel, & Thornton, ; Nathenson, Thompson, & White, ), ultimately discharging downslope at numerous springs along the eastern edge of the Shasta Valley.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations